Nutrient Stability in NASA Spaceflight Experiment Rodent Food Bars - Janani Iyer; Tyler S Marsh; Ryan J Fisher; Vandana Verma (Foods)
The Nutrient-upgraded Rodent Food Bar (NuRFB) is the standard diet for mice in NASA’s Rodent Research Project aboard the International Space Station (ISS). Given the nature of spaceflight and the lengthy production process of the food bars, a shelf-life assessment was conducted to evaluate nutritional stability over time (ranging from 0 to 27 months) and under different storage conditions (refrigerated, ambient, and refrigerated + ambient), where ambient is 22–23 °C. Lipid oxidation markers and fat- and water-soluble vitamins were assessed under various time and temperature conditions using AOAC International methods. Vitamin D levels showed a minor decrease, and riboflavin fluctuated slightly over time, but all vitamin levels remained above National Research Council (NRC) minimum requirements. Food bars stored at 4 °C showed significantly higher thiamine levels than the bars that underwent some degree of ambient temperature storage, but all met the NRC guidelines. Minimal lipid oxidation was observed for up to 18 months, and no mold or yeast growth occurred despite the high moisture content of the bars. This study confirms that NuRFBs maintain stable vitamin and lipid oxidation indices, ensuring adequate nutrition for rodents during spaceflight.